The legal analysis of the film The Voice of Equality. A case of an axiological gap in tax law - Lara Márquez, Jaime (2020)
The author analyzes the film The Voice of Equality, based on the life of U.S. Supreme Court Justice Ruth Bader Ginsburg. The work focuses on the case of Charles Moritz vs. the Internal Revenue Service, defended by Ginsburg at the beginning of her career. It was disputed whether the income tax assessment made on Mr. Moritz’s expense deduction was allowable. Under U.S. law, unmarried daughters who were employed outside the home were entitled to deduct guardianship expenses. Mr. Moritz was unmarried, cared for his mother, and was employed outside the home, but he was not a daughter, but a son, which is why the tax office denied the deduction. The lawyer’s strategy was to allege gender discrimination against her client, since the law unfairly presumed that it was the daughters who were responsible for the care of the parents. Her objective was to obtain a declaration of unconstitutionality of Article 214 of the U.S. Tax Code, for violation of the principle of equal protection before the law; and then to sue, case by case, for the unconstitutionality of one hundred and seventy-eight U.S. laws that discriminated against women.